2013
DOI: 10.1111/ijsa.12013
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Effectiveness of Error Management Training for Developing Negotiation Skills

Abstract: This study investigated whether the effectiveness of an error management approach to training negotiation knowledge and skill depended on individual differences in conscientiousness, extraversion, and openness to experience. Participants were randomly assigned to two training programs that incorporated key elements of an error management and behavioral modeling approach to training, and were trained in the complex interpersonal skill of negotiation. At the end of training, declarative knowledge acquisition, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Tasks similar to training tasks showed a smaller effect size favoring error management training (Cohen's d = 0.20; Keith & Frese 2008). More recent studies yielded similar effect sizes (Carter & Beier 2010, Cullen et al 2013, Loh et al 2013). Thus, empirical research suggests that encouraging exploration and errors during training benefits learning more than providing detailed guidance and error avoidance, particularly if the goal is to transfer the training content to difficult tasks.…”
Section: Learning From Errorsmentioning
confidence: 65%
“…Tasks similar to training tasks showed a smaller effect size favoring error management training (Cohen's d = 0.20; Keith & Frese 2008). More recent studies yielded similar effect sizes (Carter & Beier 2010, Cullen et al 2013, Loh et al 2013). Thus, empirical research suggests that encouraging exploration and errors during training benefits learning more than providing detailed guidance and error avoidance, particularly if the goal is to transfer the training content to difficult tasks.…”
Section: Learning From Errorsmentioning
confidence: 65%
“…Some individual differences, such as cognitive ability, have been examined in a number of active learning studies, whereas others, such as personality, have received much less attention. In addition, the few studies that have examined personality have sometimes produced conflicting findings (e.g., Cullen, Muros, Rasch, & Sackett, 2013;Gully, Payne, Kiechel, & Whiteman, 2002). This may be because past research has tended to focus on multifaceted active learning interventions, in which case the effects of individual differences will depend on the specific design elements that comprise the intervention and the emphasis these elements receive during training.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Blume et al ’s () meta‐analysis of the transfer literature identified cognitive ability as the strongest predictor of training transfer, showing that those with higher cognitive ability are significantly more likely to retain and generalize training concepts; to mediate low cognitive abilities research suggests increasing trainee motivation and self‐efficacy (Bhatti & Kaur, ; Grohmann et al , ). Motivation and self‐efficacy can be enhanced through the structure of the training program itself, by promoting strategies such as behavioral modeling, which involves a guided explanation of the new skills by providing models to show the correct use and teaching participants how to avoid errors (Grossman & Salas, ), error management, a more active technique, which encourages participants to make mistakes and use them as learning opportunities (Cullen, Muros, Rasch, & Sackett, ), and implementing a realistic training environment (Bhatti & Kaur, ; Grossman & Salas, ; Leimbach, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, trainings differ in terms of their effectiveness for adaptive knowledge transfer. For example, BMT has been used extensively in SAP implementation and was found to be more effective for trainees with lower cognitive ability or with previous experience with the training subject (Allen, ; Cullen et al , ; Reisslein et al , ). When the task or topic to be trained covers a relatively small amount of material that is highly structured and less complex, behavioral modeling may be an economical approach to teach the correct strategies but should be paired with opportunities for the trainees to use the new skills in ways that relate to their job contexts (Grossman & Salas, ; Keith & Frese, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation